Improvement in the Mechanical Properties of High Temperature Shape Memory Alloy (Ti50Ni25Pd25) by Copper Addition. (9th March 2015) - Rehman, Saif ur; Khan, Mushtaq; Khan, A. Nusair; Jaffery, Syed Husain Imran; Ali, Liaqat; Mubashar, Aamir
Abstract : High temperature shape memory alloys Ti50 Ni25 Pd25 and Ti50 Ni20 Pd25 Cu5 were developed, characterized, and tensile tested in both martensite (  M f − 50°C) and austenite (  A f + 50°C) phases. The transformation temperatures of ternary Ti50 Ni25 Pd25 alloy were increased by 11 to 12.5°C by substitution of Ni with 5 at% Cu. At the same time, transformation heat absorbed and released during forward and reverse martensitic transformation was also increased. In the martensite phase, the mechanical properties, that is, the stress for reorientation of martensite variants and fracture stress, were increased by 33 and 60 MPa, respectively, whereas the fracture strain was decreased by 1.5%. In the austenite phase, the critical stress for slip and fracture stress were increased by 62 and 40.9 MPa, respectively, whereas the fracture strain was decreased by 1.2%. The increase in both stresses was attributed to the solid solution strengthening by substitution of Ni atoms with relatively greater atomic radius of copper (Cu) atoms. The overall results suggest that the addition of 5 at% Cu in place of Ni in Ti50 Ni25 Pd25 alloy is very beneficial to improving the mechanical and shape memory properties and increasing the transformation temperatures.